Estimativa da população de Ucides cordatus em Reserva de Desenvolvimento Sustentável (RDS) - Bromenschenkel, Vanessa Cusini Spinassé (2016)
The Municipal Sustainable Development Reserve (RDS) Piraquê-açu and Piraquê-Mirim is located in Aracruz-ES municipality. Mangroves in this estuary is a very important environment for the people that living in their surroundings and survive with its resources. The land crab Ucides cordatus (Linneau 1763) is considered important to the mangrove ecosystem and is a livelihood resource for various traditional and indigenous communities, requiring the development of long term studies on the population in order to contribute to the management. Others studies on land crab developed in this Estuarine System showed important information and indicated the need for current analyzes that assist the sustainability actions to managing the resource, ensuring the maintenance of inventories at adequate levels. This study made samplings in 18 fixed plots (10 x 10m) in fringe and basin forests in the Estuarine System of Piraquê-açu and Piraquê-mirim rivers during low-water in spring tide, from April to June in 2015. It was counted open and closed burrows numbers to obtain data for the moulting period and density of the individuals. The diameters of burrows were evaluated, in order to indirectly estimate the sizes of the carapace of individuals. The sampling of individuals was random and used to obtain the male and female ratio. The environmental parameters evaluated were salinity and analysis of sediment (grain size and O.M.). The average population density was 0.74 ± 0.24 ind./m². Kruskal-Wallis test showed no significant difference between the values of average densities by rivers and by types of forest. The commercial density was 0.10 ± 0.05 ind./m². The male/female ratio was approximately 2:3. The total counted burrows had 61% closed and 39% open, indicating likely molting period of the species. The average size of the carapace obtained in this study is below the minimum permissible size (60 mm) by law to capture. The values of the average population density and commercial density are lower than in other regions of the country, indicating decline this feature probably due to overexploitation. We recommended actions to aimed at better monitoring and maintenance of natural stocks of this specie.